2013
DOI: 10.1007/s11090-013-9438-8
|View full text |Cite
|
Sign up to set email alerts
|

3D Unsteady State MHD Modeling of a 3-Phase AC Hot Graphite Electrodes Plasma Torch

Abstract: International audienceWe present, in this paper, the magnetohydrodynamic (MHD) modeling of a three-phase plasma torch. The MHD equations are solved using CFD software Code Saturne®, a computational fluid dynamics software which is based on colocated finite volume. The model developed is 3-D, time dependent, and assumes Local Thermodynamic Equilibrium (LTE). Regarding numerical issues, the modeling of the three-phase AC discharge is particularly tricky since the arcs ignition, by the rotating electrical potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…T = T h = T e ) are more commonly used that thermodynamic nonequilibrium (NLTE) models, particularly for the modeling of thermal plasmas (e.g. [81][82][83][84][85][86]). Nevertheless, thermodynamic nonequilibrium (two-temperature) models have been the only ones so far capable to capture the spontaneous formation of patterns in thermal plasma systems (see section 4.3 and [87,88]).…”
Section: Nonequilibrium Plasma Flow Modelsmentioning
confidence: 99%
“…T = T h = T e ) are more commonly used that thermodynamic nonequilibrium (NLTE) models, particularly for the modeling of thermal plasmas (e.g. [81][82][83][84][85][86]). Nevertheless, thermodynamic nonequilibrium (two-temperature) models have been the only ones so far capable to capture the spontaneous formation of patterns in thermal plasma systems (see section 4.3 and [87,88]).…”
Section: Nonequilibrium Plasma Flow Modelsmentioning
confidence: 99%
“…For different industrial uses such as nanoparticle synthesis, material treatment pyrolysis, gasification, waste treatment, plasma-assisted combustion, Rehmet et al (2013) proposed to use a plasma torch with 3-phase AC hot graphite electrodes arranged in the same plane. They showed that the mass flow emanating from the electrodes jets controls the arc motion and the shape of the postdischarge plasma flow.…”
Section: Refractory Oxides and Carbidesmentioning
confidence: 99%
“…There are several ways to enlarge an arc plasma volume to meet its applications in various fields, [15][16][17][18][19][20][21][22][23][24][25][26][27] including coal pyrolysis, [17,18] preparation of glass, [19][20][21] thermal spray [22,23] and spheroidization of alumina powder. [24,25] Unlike conventional linear plasma torches, a V-type plasma torch can pro-duce two separate arc columns, cathode arc column (CAC) and anode arc column (AAC).…”
Section: Introductionmentioning
confidence: 99%
“…[17,18] The use of multi-phase AC arc torch can also achieve the purpose of expanding the high-temperature region of arc plasma. [19][20][21]26,27] The initial multi-phase AC arc torch was powered by a 3-phase power supply. [26,27] Although the high-temperature region is expanded in this 3-phase arc torch, there are significant differences among the discharge intensities of multiple arcs due to low frequencies of arc currents causing the remarkable phase transition, which results in the intermittent discharge and arc instability.…”
Section: Introductionmentioning
confidence: 99%